Tick infestations on sheep and goats in the black sea region of Türkiye - Aydin, Mehmet Fatih; Aktaş, Münir; Dumanli, Nazir (Veteriner Fakultesi Dergisi, 2012)
This study was carried out to determine the status of tick infestation of sheep and goats in some cities (Bolu, Kastamonu, Çorum, Samsun, Tokat, Giresun and Bayburt) in the Black Sea region of Türkiye. For this purpose, a total of 2608 small ruminants (2161 sheep, 447 goat) in 53 town were examined in the period of 2010-2011 and 812 of them (665 sheep, 147 goat) were infested. Whole body parts of the animals were examined and 2797 ticks belong to five genus and 12 species [Rhipicephalus turanicus (28.63%), Haemaaphysalis parva (22.59%), Rhipicephalus bursa (18.26%), Dermacentor marginatus (16.55%), Rhipicephalus sanguineus (3.32%), Ixodes ricinus (2.46%), Haemaphysalis punctata (2.35%), Hyalomma marginatum (2.21%), Haemaphysalis sulcata (1.39%), Hyalomma excavatum (1.17%), Haemaphysalis concinna (0.53%), Hyalomma detritum (0.46%)] were collected. İnfestation rates in sheep and goats were 30.77% and 32.88% respectively. It was found that R. turanicus, H. parva and R. bursa were the dominant species on sheep and goats in the region. Seasonal distribution of identified tick species was also determined. Rhipicephalus and Hyalomma species were detected in spring and summer while Haemaphysalis in winter, spring and autumn and Dermacentor and Ixodes in all seasons on sheep and goats in this region. © 2012, Veteriner Fakultesi Dergisi. All rights reserved.
Türkiye’nin karadeniz bölgesindeki koyun ve keçilerde kene enfestasyonları
Keywords: Black Sea Region; Goat; Seasonal distribution; Sheep; Tick; Türkiye